Exploring dual disclosures for men who have sex with men in Mpumalanga, South Africa: a report from the field. Issue 1 (2nd January 2018) - Daniels, Joseph; Lane, Tim; Maleke, Kabelo; Mogos, Wini; Assaf, Ryan; Struthers, Helen; McIntyre, James; Coates, Tom
Abstract : We explored to whom rural men who have sex with men (MSM) disclose their sexual identity and HIV status in Mpumalanga, South Africa. Participants were recruited using a modified snowball sampling method in order to complete a questionnaire. Descriptive and logistic regression analyses were conducted. There were 47 participants of whom 22 self-reported as HIV-positive. Most participants disclosed their sexuality and HIV status to immediate family members and gay-identified friends. We found that the longer someone had identified as MSM, the more likely they were to be HIV-positive and not go to clinic. Education and employment modified these findings. This study presents a broader picture of MSM in this rural African setting: that they do disclose their sexuality and HIV status to others in their community. However, more research is needed to develop these measures. We need to assess how long participants identify as MSM, how long they have been HIV-positive, and to whom they have disclosed these aspects of their lives to inform HIV prevention and treatment interventions for MSM in rural settings.